Laboratory evaluation and interpretation of haemostasis in small animals - MISCHKE, R. (Journal of the Hellenic Veterinary Medical Society, 2017)
This review deals with indications for performing haemostasis tests, methodical aspects of blood sampling and handling of sample material, selection of appropriate tests and basic principles of test interpretation. Indications for laboratory evaluation of haemostasis in small animals include spontaneous bleeding or bleeding disproportionate to the degree of trauma, bleeding from multiple sites and diseases which are frequently associated with haemostatic disorders. Patient history and clinical findings can deliver clues for the type of haemorrhagic diathesis. Important preanalytical issues include prevention of prolonged venous stasis, order of drawing and appropriate filling of the collection tubes and careful mixing of blood with anticoagulant. Initial screening can be performed by global tests of haemostasis including viscoelastic testing using thrombelastography and rotation thrombelastometry and/or a “basic examination profile” including platelet count, capillary bleeding time (optional in cases of suspected functional platelet disorders) and group tests prothrombin time (PT), activated partial thromboplastin time (aPTT), and thrombin (clotting) time (optionally in cases of prolonged PT and aPTT). This procedure allows a rational evaluation of the haemostatic system and a specific use of further tests including individual coagulation factor activities, inhibitor activities, activation markers, examination of von Willebrand factor, and platelet function analyses. It is important (1) to use species- and method specific reference values for interpretation and (2) to consider the limitations of tests when performed according to the standard test procedure optimised for human sample material (e.g., low sensitivity of PT test for canine and feline samples).